Tes kemampuan pointing high lob atlet petanque di club DBL lombok timur tahun 2025 - Putra Pratama; Susi Yundarwati; Jamaludin (Journal Transformation of Mandalika, e-ISSN: 2745-5882, p-ISSN: 2962-2956, 2025)
Problem statement this research The sport of petanque aims to get closer to a target called a jack. The pointing high lob throw is effectively used on all terrains and all distances in the petanque game. So the researcher aims to determine the level of High Lob pointing ability and consistency of East Lombok DBL petanque athletes.This type of research is descriptive with quantitative research methods. The sample from this study consisted of 12 DBL East Lombok petanque athletes. Data collection in this study carried out a test with a fixed target pointing instrument which had been tested for validity of 0.783 and reliability of 0.756. The data analysis technique uses Anas Sudijono's 5 scales of research norms.The research results showed that the overall average pointing high lob distance of DBL East Lombok male petanque athletes at a distance of 6 meters was an average point of 11.9 (79%) in the very good category, a distance of 7 meters had an average point of 9.7 (67%) in the good category, a distance of 8 meters had an average of 10 points (67%) in the good category, a distance of 9 meters had an average of 8.3 points (55%) in the good category. And the results for female athletes were produced at a distance of 6 meters, namely an average of 9.9 points was produced in the very good category with a percentage of 66%, at a distance of 7 meters an average of 8.3 points was produced in the good category with a percentage of 55%, at a distance of 8 meters an average of 7.7 points was produced in the good category with a percentage of 51%, at a distance of 9 meters an average of 5.6 points was produced in the fair category with a percentage of 37%.The results of the tests carried out by DBL East Lombok.